Alliance capability, stock market response, and long‐term alliance success: the role of the alliance function - Kale, Prashant; Dyer, Jeffrey H.; Singh, Harbir (Strategic Management Journal, 2002)
This paper addresses two key questions: (1) what factors influence firms' ability to build alliance capability and enjoy greater alliance success, where firm‐level alliance success is measured in two ways: (a) abnormal stock market gains following alliance announcements and (b) managerial assessments of long term alliance performance; and (2) are the two alternate ways of assessing alliance success correlated? We find that firms with greater alliance experience and, more importantly, those that create a dedicated alliance function (with the intent of strategically coordinating alliance activity and capturing/disseminating alliance‐related knowledge) realize greater success with alliances. More specifically, firms with a dedicated alliance function achieve greater abnormal stock market gains (average of 1.35%) and report that 63 percent of alliances are successful whereas firms without an alliance function achieve much lower stock market gains (average of 0.18%) and only a 50 percent long‐term success rate. We also find a positive correlation between stock market‐based measures of alliance success and alliance success measured through managerial assessments. In addition to providing insights into the development of alliance capability among firms, this paper is one of the first to provide empirical support for the efficient markets argument by demonstrating that the initial stock market response to a key event positively correlates to the long‐term performance and value of the event. Copyright © 2002 John Wiley & Sons, Ltd.